Analysis of top management support, project management, and user engagement influence on enterprise resource planning system implementation - Afdhal; Muthia Roza Linda (Operations Management and Information System Studies, 2021)
This research aims to analyze: (1) the influence of top management support on the implementation of enterprise resource planning (ERP) on pt Telkom Indonesia Padang company, (2) The influence of project management against the implementation of enterprise resource planning (ERP) on PT Telkom Indonesia Padang company, (3) The influence of user engagement on the implementation of enterprise resource planning (ERP) on PT Telkom Indonesia Padang company. The population in this study is all employees who use enterprise resource planning systems with a total of 120 employees. The sampling technique used is a census method in which the entire population will be sampled. The research data collected using questionnaires were then analyzed with a multiple linear regression approach using SPSS software. This research is different from other studies, where the difference is the selection of erp implementation success factors, where most similar studies or similar research objects rarely use project management factors, and user engagement as a success factor of ERP systems is seen from various previous studies that have been done by several researchers. The results of this study show that (1) top management support has a significant effect on the implementation of enterprise resource planning systems, while (2) project management, and (3) user engagement have no significant effect on the implementation of enterprise resource planning systems.